Form Of Implementation Of Good Corporate Govarnance Principles At Laznas Wahdah Inspiration - Ramadan, Muhammad Fajar; Busyairi, Ahmad; Sirajuddin, Sirajuddin; Kara, Muslimin; Anwar, Nurfiah; Muin, Rahmawati; Katman, Muhammad Nasri (LP2M IAIN Palopo, 2024)
The country with the largest Muslim population makes Indonesia have a large zakat potential, namely 233 trillion, but this large potential is inversely proportional to what has been collected, namely only 1% of the potential or 10 trillion. The implementation of GCG is considered to be one solution to increase the realization of zakat. the. Wahdah Inspirasi Zakat (WIZ) is a Laznas that shows collection performance that has increased significantly, which is the basis for the author to conduct research to find out what form of GCG implementation in WIZ Makassar City is based on guidelines.good governance published by the National Committee for Governance Policy (KNKG). This research is qualitative with a phenomenological approach. The results of the research show that WIZ has implemented GCG well in accordance with the provisions issued by the National Committee for Governance Policy (KNKG), but at the point of transparency there is one indicator that has not been fulfilled optimally, namely the absence of detailed financial reports on the internet network so that This means that the principle of transparency is not perfectly implemented, but this is fine because it is not required according to Law No. 23 of 2011 but only requires periodic reporting to the government, in this case Baznas and the Ministry of Religion